2004
DOI: 10.1128/jcm.42.12.5819-5824.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of gyrA and parC Mutations Associated with Ciprofloxacin Resistance in Neisseria gonorrhoeae by Use of Oligonucleotide Biochip Technology

Abstract: An oligonucleotide biochip that specifically detects point mutations in the gyrA and parC genes of Neisseria gonorrhoeae was designed and subsequently evaluated with 87 untreated clinical specimens. The susceptibilities of the N. gonorrhoeae strains were tested to determine the prevalence of ciprofloxacin-resistant strains in Anhui Province, People's Republic of China. Conventional DNA sequencing was also performed to identify mutations in gyrA and parC and to confirm the biochip data. The study demonstrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(34 reference statements)
1
21
0
2
Order By: Relevance
“…A correlation between levels of ciprofloxacin resistance and the location and number of mutations in the gyrA and parC genes has been observed in different studies (21,30,35), although it has not been found in others (19,29).…”
Section: Discussionmentioning
confidence: 96%
“…A correlation between levels of ciprofloxacin resistance and the location and number of mutations in the gyrA and parC genes has been observed in different studies (21,30,35), although it has not been found in others (19,29).…”
Section: Discussionmentioning
confidence: 96%
“…exclusively associated with gyrA mutations (11,12). Furthermore, parC mutations in isolation do not appear to be associated with antimicrobial resistance (19). On the basis of these data and reported estimates of clinically significant resistance for 500 mg of ciprofloxacin ranging between 0.125 and 1.0 mg (10), we restricted our assay to the detection of mutations in the Ser91 region of the gyrA gene.…”
Section: Figmentioning
confidence: 99%
“…More than 99% of QRNG specimens have been shown to have mutations at this site of the gyrA gene (18,19). This method allows for rapid detection of QRNG without complex laboratory techniques or extensive resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The oligonucleotide chips were incubated at 40℃ for 30 min in a moist incubator. After hybridization, the washing procedure was carried out as described in our previous research [9] . The oligonucleotide chip images were obtained with a fluorescent scanner (GenePix 4000B; Axon Instruments, Inc., Calif).…”
Section: Oligonucleotide Chips Fabricationmentioning
confidence: 99%